Moulding three-dimensional curved structures by selective heating. Issue 2 (26th February 2020) - Jain, Harsh; Ghosh, Shankar; Nitsure, Nitin
Abstract : It is of interest to fabricate curved surfaces in three dimensions from homogeneous material in the form of flat sheets. The aim is not just to obtain a surface which has a desired intrinsic Riemannian metric, but to get the desired embedding in R 3 up to translations and rotations. In this paper, we demonstrate three generic methods of moulding a flat sheet of thermo-responsive plastic by selective contraction induced by targeted heating. These methods do not involve any cutting and gluing, which is a property they share with origami. The first method is inspired by tailoring, which is the usual method for making garments out of plain pieces of cloth. Unlike usual tailoring, this method produces the desired embedding in R 3 . The second method just aims to bring about the desired new Riemannian metric via an appropriate pattern of local contractions, without directly controlling the embedding. The third method is based on triangulation, and seeks to induce the desired local distances. This results in getting the desired embedding in R 3 . The second and the third methods, and also the first method for the special case of surfaces of revolution, are algorithmic in nature. We explain these methods and show examples.